Penerapan Metode Problem Based Learning Pada Mata Kuliah Pancasila Untuk Meningkatkan Kompetensi Mahasiswa Teknik Informatika - Kristiningsih, Kristiningsih; Widaryanto, Eko (Faculty of Teacher Training and Education of Undaris, 2025)
Pancasila Education is an education about political democracy that aims to educate students to act democratically based on Pancasila and the 1945 Constitution (UUD). One of the learning methods that can be applied to the course is Problem Based Learning. This model can overcome the problem of the ability to understand concepts and apply Pancasila values in society. Current technological developments make information more easily accessible to the public. Therefore, awareness and ability are needed from those who access the digital world, especially students, to analyze and process information related to Pancasila issues so that its credibility can be accounted for. This study aims to describe the problems of students in processing information and assess students' abilities in responding to information related to Pancasila issues. This study is a qualitative study using a case study method. The study began with an interview and continued with the orientation, exploration, and member check stages. There are several difficulties faced by students in choosing discussion materials on the theme of Pancasila, including many students who are not careful and are fooled by provocative titles, do not examine the website address, do not check the source of the facts, do not check the authenticity of the photos. Providing a method through discussion helps students to quickly respond to the information provided. They can also process and make arguments on Pancasila issues.Keywords: Learning Methods, Digital, Information, Pancasila Education